Do callable convertibles support the investment process of a company? An analysis of the world market of hybrid debt - Damian Kaźmierczak (Comparative Economic Research. Central and Eastern Europe, 2017)
Using a sample of 1,705 convertible bonds issued by manufacturing and service companies from the United States (1,138 issues); Europe (270); and Asia (297) between 2004 and 2014 this paper investigates the role of callable convertibles in the corporate investment process. This research shows first that callable convertibles are used to finance investment projects particularly by American firms which may exercise new investment options to improve poor financial performance. Secondly, the same strategy may be followed by European companies, but they seem not to carry out investments on as large a scale as American firms. Thirdly, the research results do not provide evidence that Asian enterprises use callable convertibles for investment purposes: they likely use these instruments for different reasons.
Keywords: G15; G23; G31; 330; debt financing; investment opportunities; callable convertible bonds